The Role of Pancasila in Elementary Schools to Face the Challenges of the Disruption Era - Fara Diba Catur Putri (Universitas Sebelas Maret, 2021)
This study aims to determine the role of Pancasila in the era of disruption to be an important part that every individual must realize that this era must be passed and become a challenge in current developments. Changes that are increasingly fast are encouraging and requiring us to innovate. The ability to innovate is one strategy in maintaining our existence in this era. The development of this era has an impact on various existing fields, one of which is education. Education is an important aspect which is one of the means to achieve the national goals of the Indonesian nation. The method used is a qualitative descriptive case study research method for elementary school students in South Jakarta. The data source is elementary schools in Pasar Minggu sub-district. The research data is in the form of descriptions of the utterances of several informants who describe the role of Pancasila. The subjects of this study were elementary school students in Pasar Minggu sub-district with the object, namely 50 students and 10 class teachers. The results showed that the role of civic education for elementary school students and learning civics education is fun. Thus, creating a new paradigm even though the times are increasingly rapid, elementary school students still instill character values according to the noble culture of courtesy and ethics. The function of civic education is implemented in a habit of anticipating and overcoming moral crises in elementary school students in South Jakarta.